(untitled) (Stato, Chiese e pluralismo confessionale, 2017)
SOMMARIO: 1. L’autonomia scolastica e il modello italiano - 2. Gli ostacoli alla realizzazione di tale modello e le premesse per un suo rilancio - 3. L’autonomia scolastica in una nuova prospettiva delle autonomie locali. ABSTRACT: The paper examines school autonomy with specific reference to the organizational profile that is considered in the light of the recent reform introduced with L. 13 July 2015 n.107. In particular, premised a brief explanation of the school system as outlined in the Italian law, it is examined the model currently in force and its compatibility with the guidelines resulting from the Constitutional Charter, i.e. with artt.33 and 34 Cost., as rules protecting the right to education, to qualify as a fundamental right, as well as with artt. 2, 117 and 118 of the Constitution. Considering this legal basis, the paper proposes a redefinition of the division of powers between the State and Regions in the field of school autonomy, in the aim to draw a new organizational model that looks at a development of local autonomy which venues where you can better identify the needs of the communities.